Behavioral risk factors for STD/HIV transmission in Bangladesh's trucking industry - Gibney, Laura; Saquib, Nazmus; Metzger, Jesse (Social science & medicine (1982), 2003)
To examine behaviors that could influence STD/HIV transmission in Bangladesh's trucking industry, a survey was orally administered to 388 truck drivers/helpers at Tejgaon truck stand in Dhaka. A two-tiered sampling strategy was used: 38 trucking agencies were randomly selected and a mean of 10.2 subjects was recruited from each agency. Focus group and in-depth interviews were also conducted. The focus was on behaviors that affect (i) exposure to STD/HIV infection, (ii) efficiency of transmission of infection and (iii) duration of infectiousness. The findings illustrated that intravenous drug use was not an important risk factor; only 1 subject had used drugs intravenously. Sexual risk behaviors, however, were prevalent: the mean number of sexual partners in the past year was 4.57 (SD=8.70) and in the past 3 months was 1.82 (SD=3.27). Premarital and extramarital sex was common, often with commercial sex workers (CSW); 54% of all subjects had relations with at least 1 CSW in the past year. In a multiple logistic regression analysis, subjects who engaged in other types of socially risky behavior (drinking alcohol, ingesting or smoking recreational drugs, having sex with other men) were significantly ( p<0.05) more likely to have had sex with a CSW in the past year. While 7.2% of subjects had a male sex partner in the past year, 21% had ever had one (likely youthful experimentation for most). Condom use was very infrequent: of the 343 subjects who had ever had sexual intercourse only 31% had ever used a condom and most of those subjects had used only once or occasionally. Having sex with CSWs, being married, having heard of AIDS and age were significantly associated ( p<0.05) with ever use of condoms. Frequently, subjects who had genital symptoms either did not have those symptoms treated at all or treated in a timely fashion, and over 1/3 did not change their sexual behavior while infected. To reduce the potential for the spread of STD/HIV in this population, appropriate treatment practices for sexually transmitted infections need to be encouraged and condom use promoted, particularly in the context of casual sexual relations.